ANÁLISIS DEL COMPORTAMIENTO DEL COMERCIO INTERNACIONAL DE CARNE BOVINA EN EL MARCO DEL TLC COLOMBIA-ESTADOS UNIDOS EN EL PERIODO 2006-2016 - Gutierrez Giraldo, Karen Daniela (Universidad Antonio Nariño, 2024)
The analysis of the evolution of beef trade within the framework of the FTA between Colombia and the United States, in force since May 2012, is of great importance. During the period 2006-2016, notable changes were observed in beef exports and imports, influenced by factors such as global prices, regulations and consumer preferences. This study seeks to understand how the livestock industry adapted to the conditions of NAFTA and the challenges it faced. It offers a complete vision of the impacts of the agreement on the economy of both countries and highlights the relevance of trade agreements in the meat industry and the complex commercial relationships between nations. Key words: International trade, beef, free trade agreement, consumers, Colombia, United States, import, export.